PROSES MORFOFONEMIK DALAM BAHASA INGGRIS DAN BAHASA TONTEMBOAN (SUATU ANALISIS KONTRASTIF) - PIRI, GUIDO CHRISTIAN; KODONG, FENTJE; LOTULUNG, DONALD RINGGO (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACT            This research entitled ?Morphophonemic Process in English and Tontemboan Language: A Contrastive Analysis?. This research aims at identifying, analyzing and describing the morphophonemic processes in English and Tontemboan language and finding out the similarities and the differences of the morphophonemic processes by using of Crystal?s (2008) and Nida?s (1949) theories. The method used in this research is descriptive research method. Data were collected from several references some books, journals, and through the interview of some informants. The results of this research show that morphophonemic process in English and Tontemboan language has some similarities and differences. The similarities are both languages have kinds of morphophonemic processes, they are assimilation, loss of consonant phonemes, loss of vowel phonemes, palatalization, and nasalization. The differences are on the dissimilation and reduction of cluster. Other similarities and differences are found in assimilation. English has eight kinds of assimilations, those are progressive, regressive, contiguous phonemes, noncontiguous phonemes, point of articulation, manner of articulation, partial assimilation and complete assimilation whereas Tontemboan language has only seven kinds of assimilations, those are progressive, regressive, contiguous phonemes, point of articulation, manner of articulation, partial assimilation, complete assimilation and doesn?t have noncontiguous phonemes. This research is expected to give beneficial contribution both in theory and practice. Theoretically, it can give contribution to the development of linguistics (morphology), especially about morphophonemic process, and practically, the writer gets the knowledge that the encounter between morphemes. Keyword:  Morphophonemic Process, English and Tontemboan Language, Contrastive Analysis